Typization of Lakes of the East Antarctica Oases - G. V. Pryakhina; M. R. Kuznetsova; E. S. Zelepukina; A. S. Boronina; S. V. Popov; S. D. Grigoreva; A. A. Chetverova; M. P. Kashkevich; Г. В. Пряхина; М. Р. Кузнецова; Е. С. Зелепукина; А. С. Боронина; et al. (Izvestiya Rossiiskoi Akademii Nauk. Seriya Geograficheskaya, 2023)
The urgency of creating a new complex typization of lakes of the East Antarctica oases is dictated not only by the desire to summarize accumulated Antarctic lakes’ data but also by the need to obtain the most informative characteristics of lake hydrological regime in the region for solving a wide applied problems’ range. Features of lake water level changes were used as a criterion in developing the complex typization of lakes of the East Antarctica oases for the first time, in contrast to existing classifications. The study was based on the analysis of literary and archive materials (the Larsemann Hills, the Schirmacher oasis, the Banger Hills, the Molodezhnyi oasis, the Vestfold Hills, and the McMurdo Dry Valleys), as well as our own expeditionary data (field seasons of 2017–2022, the Larsemann Hills). A group of indirect criteria (presence and type of natural dam, position in the cascade, flowage type, etc.) is proposed in addition to a group of direct criteria (duration of the lake filling phase, water level rise, etc. requiring organization of field observations) to obtain a holistic view of the water level regime of lakes. It is important that characteristics of the most indirect criteria can be obtained by visual reconnaissance surveys or by maps and remote sensing data. The identified 4 types (outbursting, tendentious, transit, and tidal) and 8 subtypes of lakes were illustrated by generalized graphs of water level changes, which objectively characterize the features of the lake hydrological regime. The openness of the typization suggests the opportunities for actualization with the accumulation of new scientific knowledge and data. Актуальность создания комплексной типизации озер оазисов Восточной Антарктиды продиктована не только необходимостью учета современных накопленных данных об антарктических водоемах, но и необходимостью обобщения представлений о гидрологическом режиме озер для решения широкого спектра фундаментальных и прикладных задач. При разработке комплексной типизации озер антарктических ...